2018
DOI: 10.3389/fendo.2018.00703
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Synthetic, Neuroactive Steroid Is Effective at Decreasing Depression-Like Behaviors and Improving Maternal Care in Preclinical Models of Postpartum Depression

Abstract: Preclinical testing of treatments for postpartum depression (PPD) has been limited due to the lack of available animal models of such a complex disorder. To address this limitation, our laboratory has generated unique preclinical mouse models that exhibit abnormal postpartum behaviors. Mice with a loss or reduction in the expression of the GABAA receptor (GABAAR) δ subunit (Gabrd−/− or Gabrd+/−, respectively) and mice that lack the K+/Cl− co-transporter, KCC2, specifically in corticotropin-releasing hormone (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…Mice which lack ( Gabrd −/− mice) or have deficits in GABA A R δ subunit expression ( Gabrd ± mice) exhibit depression-like behaviors restricted to the postpartum period and deficits in maternal care (Maguire and Mody, 2008). Similar to the robust antidepressant effects of neurosteroid-based treatments in patients with postpartum depression (Kanes et al, 2017a, 2017b; Meltzer-Brody et al, 2018a), a similar compound, SGE-516, exhibits robust antidepressant effects in preclinical mouse models of postpartum depression (Melón et al, 2018). Collectively, these findings suggest that deficits in neurosteroid signaling are sufficient to induce depression-like behaviors, with potential relevance to mood disorders related to the postpartum period.…”
Section: Allopregnanolone In Postpartum Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice which lack ( Gabrd −/− mice) or have deficits in GABA A R δ subunit expression ( Gabrd ± mice) exhibit depression-like behaviors restricted to the postpartum period and deficits in maternal care (Maguire and Mody, 2008). Similar to the robust antidepressant effects of neurosteroid-based treatments in patients with postpartum depression (Kanes et al, 2017a, 2017b; Meltzer-Brody et al, 2018a), a similar compound, SGE-516, exhibits robust antidepressant effects in preclinical mouse models of postpartum depression (Melón et al, 2018). Collectively, these findings suggest that deficits in neurosteroid signaling are sufficient to induce depression-like behaviors, with potential relevance to mood disorders related to the postpartum period.…”
Section: Allopregnanolone In Postpartum Depressionmentioning
confidence: 99%
“…These behavioral impairments are thought to be due to excessive glucocorticoid signaling given that exogenous corticosterone treatment can induce deficits in postpartum behaviors (Brummelte and Galea, 2010; Brummelte et al, 2006; Maguire and Mody, 2016b), similar to effects observed with chronic stress during late pregnancy (Maguire and Mody, 2016a). Interestingly, a neurosteroid-based treatment, related to the recently FDA-approved treatment for postpartum depression, is effective at restoring normal HPA axis function and decreasing depression-like behaviors and improving maternal care in two independent preclinical models of postpartum depression (Melón et al, 2018) ( Table 1 ) .…”
Section: Allopregnanolone In Postpartum Depressionmentioning
confidence: 99%
“…Postpartum depression (PPD) is an important public health issue as it affects women at a highly vulnerable time and can affect the cognitive and emotional development of the child 112 . The risk of depression in women becomes significantly increased during the postpartum period, and nearly 20% of mothers have PPD, which is frequently preceded by antenatal anxiety- and depression-related symptoms or chronic stress as the strongest predictors 113115 . PPD is frequently attributed to a maladaptation to peripartum fluctuations in reproductive hormone levels during pregnancy and the postpartum period 116, 117 .…”
Section: Postpartum Risk Of Depressionmentioning
confidence: 99%
“…3B, black line), and these changes contribute to a hyperexcitable state (Isaacson and Scanziani, 2011) that can be manifest as stress-like and depressive-like behaviors. These behaviors can be corrected by agents that enhance tonic inhibition including NAS (Maguire and Mody, 2008; Melon et al, 2018). Interestingly, one model for postpartum psychiatric illness involves knockout/knockdown of expression of δ-subunits.…”
Section: How Do Nas Act As Antidepressants and Anxiolytics?mentioning
confidence: 99%